2012
DOI: 10.1007/s00439-012-1238-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistical effect of 20-HETE and high salt on NKCC2 protein and blood pressure via ubiquitin–proteasome pathway

Abstract: We previously generated a cytochrome P450 4F2 (CYP4F2) transgenic mouse model and demonstrated that overexpressed CYP4F2 and overproduced 20-HETE in the kidneys contribute to the increase of blood pressure in the CYP4F2 transgenic mice with normal salt intake. We currently expect to elucidate a potential mechanism of salt-related hypertension whereby diverse levels of 20-HETE interact with dietary salt on Na(+)-K(+)-2Cl(-) cotransporter, isoform 2 (NKCC2) in the kidneys of the transgenic and wild-type mice wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…This is of particular interest because NKCC2 protein expression is down-regulated by high salt intake (4) and in the aged kidney (7). Consequently, an increase in OS9 expression in response to ER stress could contribute to the down-regulation of NKCC2 expression via the ubiquitin-proteasome pathway under these conditions (4,7).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is of particular interest because NKCC2 protein expression is down-regulated by high salt intake (4) and in the aged kidney (7). Consequently, an increase in OS9 expression in response to ER stress could contribute to the down-regulation of NKCC2 expression via the ubiquitin-proteasome pathway under these conditions (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although distinct cellular mechanisms may account for NKCC2 loss of function in BS1 disease, our preliminary data in the laboratory revealed that ER-associated protein degradation is the most common mechanism underpinning BS1. 4 Consequently, understanding the involvement of this process in BS1 is essential to provide novel therapeutic strategies for the treatment of BS1. Indeed, the identification and selective modulation of ERAD components specific to NKCC2 and its disease causing mutants might help to define a strategy to release fractions of misfolded mutant proteins from the ER by preventing their interactions with the quality control components to rescue their surface expression and restore their functional activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations